Influence of Customer Quality Responsibility on Customer Acceptance and Assurance - Regmi, Suman Kumar (SXC Journal, 2025)
This paper tries to examine the influence of customer quality responsibility on customer acceptance. Data has been collected through structured questionnaires of three different sectors (manufacturing, services and agriculture). Descriptive and causal comparative research designs have been used to achieve the objectives and descriptive as well as multiple regression models to analyze the data. It is observed that, relationship with the community is the major area of customer quality responsibility and to promote a quality image is the main reason that drives the company to adopt Customer Quality Responsibility (CQR) practices. It is also deduced that all independent variables have a positive and significant relationship with customer quality acceptance.